Comunicación virtual y su influencia en el desarrollo profesional de los estudiantes de Comunicación Social de la Universidad Técnica de Babahoyo Extensión Quevedo, año 2022 - Laica Zambrano, Mónica Elizabeth (2022)
In the present investigative work, virtual communication is disclosed as a promoter of the democratization of information and the influence it has on the professional development of social communicators. Its objective is to determine virtual communication and its influence on the professional development of the students of the Social Communication career of the Technical University of Babahoyo, Quevedo extension, where the practice that communicators usually have is exposed. The students of said educational institution were analyzed regarding the aspect of professional development and the implementation of virtual communication in the various fields of social communication. In the methodology, the inductive and deductive method, the sample of 142 students was taken into account, then a descriptive analysis and bibliographic data are made, it is concluded that virtual communication has captured both space and interest in the entire population of future social communicators, that is why the students have determined that through this mode of communication there are greater possibilities of developing their knowledge when they are already professional communicators.